Costs of selfing prevent the spread of a self‐compatibility mutation that causes reproductive assurance. (1st April 2017) - Layman, Nathan C.; Fernando, M. Thilina R.; Herlihy, Christopher R.; Busch, Jeremiah W.
Abstract: In flowering plants, shifts from outcrossing to partial or complete self‐fertilization have occurred independently thousands of times, yet the underlying adaptive processes are difficult to discern. Selfing's ability to provide reproductive assurance when pollination is uncertain is an oft‐cited ecological explanation for its evolution, but this benefit may be outweighed by costs diminishing its selective advantage over outcrossing. We directly studied the fitness effects of a self‐compatibility mutation that was backcrossed into a self‐incompatible (SI) population of Leavenworthia alabamica, illuminating the direction and magnitude of selection on the mating‐system modifier. In array experiments conducted in two years, self‐compatible (SC) plants produced 17–26% more seed, but this advantage was counteracted by extensive seed discounting—the replacement of high‐quality outcrossed seeds by selfed seeds. Using a simple model and simulations, we demonstrate that SC mutations with these attributes rarely spread to high frequency in natural populations, unless inbreeding depression falls below a threshold value (0.57 ≤ δthreshold ≤ 0.70) in SI populations. A combination of heavy seed discounting and inbreeding depression likely explains why outcrossing adaptations such as self‐incompatibility are maintained generally, despite persistent input of selfing mutations, and frequent limits on outcross seed production in nature.